Another world is possible : spiritualities and religions of global darker peoples - Hopkins, Dwight N.; Lewis, Marjorie (London ; Oakville, CT : Equinox Pub., 2009)
"Another World is Possible: Spiritualities and Religions of Global Darker Peoples represents voices of darker skin peoples throughout the world. What they have in common is their mobilizing their own created religions and spiritualities to forge self-identities. Some claim direct links to centuries of indigenous spiritual practices which have survived relatively in tact despite the invasion of foreign religions. Others have appropriated externally introduced religions and greatly modified these belief systems by combining or syncretizing them with indigenous perspectives and practices. All authors indicate the celebration and positive utility of their communities' spiritualities and religions. Without them, not only would individuals have died, but entire cultures and contexts would have perished. Thus, religion and spirituality suggest survival and pragmatic purposes. From creation narratives to Trickster heroes and heroines, spirituality and religion incarnate meaning, as well as fashion meaning so that humans can make surviving and thriving sense of the ecology and all breathing realities. The gods, God, and ancestors give life to peoples and their cultures, ecologies, and economies, all in the service of aiding the human community to be more fully human as servants to what spiritualities and religions have facilitated on earth. This book speaks to the progressive role of spiritualities and religions for today. In that sense, it is a gift to the world from the darker skin peoples globally."--Back cover.
Includes bibliographical references (pages [371]-372) and indexes.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Blacks -- Religion; Religions; Spirituality; Electronic books